Activation of TRPV4 by lactate as a critical mediator of renal fibrosis in spontaneously hypertensive rats after moderate- and high-intensity exercise - Zhao, Binyi; Xu, Yanping; Chen, Yunlin; Cai, Ying; Gong, Zhiyan; Li, Dan; Kuang, Hongyu; Liu, Xiaozhu; Zhou, Hao; Liu, Guochun; Yin, Yuehui (Frontiers in Physiology, 2022)
Moderate-intensity exercise training has been regarded as a healthy way to alleviate kidney fibrosis by transforming growth factor-beta (TGFβ) signaling pathway. However, the impact of different intensity exercise training on renal function is unknown, and the underlying mechanism is also unclear. The purpose of this study is to explore the effect of lactic acid in different intensity exercise training on renal fibrosis in spontaneous hypertension. Masson’s trichrome staining, immunohistochemistry, lactic acid kit, western blotting were applied on the excised renal tissue from 6 male Wistar-Kyoto rats (WKY) and 18 male spontaneously hypertensive rats (SHR), which were randomly divided into a sedentary hypertensive group (SHR), moderate-intensity exercise hypertensive group (SHR-M), high-intensity exercise hypertensive group (SHR-H). The results revealed that renal and blood lactic acid, as well as the key fibrotic protein levels of transient receptor potential vanilloid 4 (TRPV4), TGFβ-1, phospho-Smad2/3 (p-Smad2/3), Smad2/3 and connective tissue growth factor (CTGF) were significantly decreased in the SHR-M group when compared with the SHR and SHR-H group. In further vitro experiments, we selected Normal rat kidney interstitial fibroblast (NRK-49F) cells. By immunofluorescence and western blotting techniques, we found that TRPV4 antagonists (RN-1734) markedly inhibited lactate-induced fibrosis. In conclusion, high-intensity exercise training (HIET) can cause the adverse effects (renal damage and fibrosis). High concentrations of lactic acid can aggravate renal fibrosis conditions via activating TRPV4-TGFβ1-SMAD2/3-CTGF-mediated renal fibrotic pathways in spontaneous hypertension.